Penilaian dan Prediksi Indeks Kualitas Air Sungai Asam, Kota Jambi - Lailal Gusri; Lilis Suryani; Shally Yanova; Bambang Irawan; M. Nuklirullah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The water quality of rivers can deteriorate due to the large amount of pollutants entering the river. Water quality assessments provide an overview of the actual state of water quality. The WQI can provide valuable information about the water quality of rivers. The calculation of the water quality index is carried out because there is a high probability that other parameters also exceed the quality standards, which are not considered when calculating the water quality index. Therefore, it is very important to assess the water quality of the river. The objective of this study was to assess the water quality of the Asam River, Jambi City. The research methodology involved collecting water samples from the Asam River at locations I (upstream), II (middle) and III (downstream) and testing the samples in the laboratory. Indices were analyzed using WQI for the following variables: temperature, total suspended solids (TSS), pH, BOD, COD, nitrate, total phosphate, dissolved oxygen and fecal coliforms. The method using WQI to determine water quality classification values ​​can serve as a reference for problem solving and evaluation of water pollution management. The results based on the calculations resulted in a WQI value of 96,27 at location II (middle); 70,95 at location I (upstream) and 186,01 at location III (downstream). The results of the study on the water quality of the Asam River are as follows: 1) very low water quality, 2) low quality water and 3) unfit for drinking water, posing a risk to aquatic life and human health.